A chemical dynamic model for the infiltration of outdoor size‐resolved ammonium nitrate aerosols to indoor environments. (13th December 2019) - Xie, Yangyang; Zhao, Bin
Abstract: In the present study, we developed a chemical dynamic model to describe the infiltration of size‐resolved ammonium nitrate aerosols from outdoor to indoor environments. This model considered the penetration factor, deposition rate, and the reversible reaction process, which was quantified by the diffusive molar flux on the surface of ammonium nitrate aerosols depending on indoor temperature, humidity, and concentrations of nitric acid (HNO3 ) and ammonia (NH3 ). To verify the model, we employed a single‐particle aerosol mass spectrometer with an automated switching system to simultaneously measure size‐resolved outdoor and indoor ammonium nitrate aerosols. Comparisons between the predicted and measured concentrations of these aerosols showed a mean relative error of 4.8 ± 18.3%. To analyze the sensitivity of model parameters, several parameters were perturbed. This analysis indicated that parameters related to HNO3 were more sensitive than those related to NH3 because the indoor gas phase concentration of NH3 was much higher than that of HNO3 .